2022
DOI: 10.3389/feart.2022.891319
|View full text |Cite
|
Sign up to set email alerts
|

Looking Into the Entanglement Between Karst Landforms and Fault Activity in Carbonate Ridges: The Fibreno Fault System (Central Italy)

Abstract: The entanglement between active tectonics and karst systems is well-known in the literature. Karst systems are sound recorders of continental deformation in terms of brittle structures and seismic features and have been successfully used as markers for reconstructing tectonic stresses and assessing preferential directions of increased permeability in oil and gas fields. Karst systems could also be exploited to evaluate the past activity of faults bounding karst hydrostructures, thus providing useful data for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…According to the aforementioned authors, the thrust activity here ended in the Pliocene, followed by a transcurrent phase and then by extensional phase. The Differently from Carrara et al (1995a, b), Saroli et al (2006Saroli et al ( , 2012Saroli et al ( , 2022 defined fault activity as persistent throughout the Quaternary, at least along the southern fault segment (Figure 2B), named as the Posta Fibreno Fault. According to these authors, the fault activity and the related deformation field conditioned a NW-SE distribution of the dolines, pervasively distributed in the carbonate reliefs of the study area.…”
Section: The Roveto Valleymentioning
confidence: 92%
See 3 more Smart Citations
“…According to the aforementioned authors, the thrust activity here ended in the Pliocene, followed by a transcurrent phase and then by extensional phase. The Differently from Carrara et al (1995a, b), Saroli et al (2006Saroli et al ( , 2012Saroli et al ( , 2022 defined fault activity as persistent throughout the Quaternary, at least along the southern fault segment (Figure 2B), named as the Posta Fibreno Fault. According to these authors, the fault activity and the related deformation field conditioned a NW-SE distribution of the dolines, pervasively distributed in the carbonate reliefs of the study area.…”
Section: The Roveto Valleymentioning
confidence: 92%
“…Carrara et al (1995a, b) stated that displacements along the fault have been supposed only for the Early Quaternary, implying the current fault's inactivity. By contrast, other authors considered the fault as active during the whole Quaternary (Roberts and Michetti, 2004;Papanikolaou et al, 2005), and more recently, recent activity has been demonstrated for the southern prolongation of the fault (i.e., the Posta Fibreno fault; Saroli et al, 2022), while further investigations defined the inactivity of the northernmost sector . These aspects are by no means trivial as for the evaluations on the fault capability, since villages are settled along the fault (Pescosolido, Balsorano, San Vincenzo Valle Roveto, Morrea, Civita d'Antino, Capistrello, etc.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…1). Normal fault exposures have been detected along its eastern flank, i.e., along the northern prolongation of a 24-km-long fault (Middle Liri Valley-Posta Fibreno fault, being part of Liri fault) which has been considered as active during the Late Quaternary (Saroli et al 2003(Saroli et al , 2006(Saroli et al , 2022Dixit Dominus 2020). However, recent activity of the northernmost segments of the Liri fault is debated and will be the object of Sect.…”
Section: Geological and Seismological Frameworkmentioning
confidence: 99%